This Could Be Heaven or This Could Be Hell: Escape and Anxiety in the Cinematic Hotel. - Nechamkin, Sarah. (Tufts Archival Research Center, 2018)
An in-depth look at the role of the hotel in contemporary American cinema through four films - The Shining, Psycho, The Grand Budapest Hotel, and Lost in Translation - and how they depict the hotel as a paradoxical site of both fantasy and distress.